Marketing social corporativo e identidade corporativa na perspectiva do gestor : um estudo multicasos na indústria alimentícia do Paraná - Corrêa, Patricia Soares Azoline (2007)
The corporate social marketing is a concept originated in the 90s and that brings together corporate social responsibility elements and marketing tools, so it aims to share value among the companies? publics, through the communication of the social programs, in a process that benefits not only for the cause as well as the company itself. Including the social values, proposed by the corporate social marketing in the communication, it is believed that can occur an influence in the identity of the companies because they present themselves differently to their publics. So, in this dissertation, the main objective is to study, in the managers? perspective, the influence of these social programs in the corporate identity in the biggest food industries in the state of Paraná, though the communication process. To achieve this objective, in the first moment, it is done a theoretical discussion about the main concepts which drive to the formulation of the empirical part, consisted in a qualitative research, applied between december, 2006 and march, 2007, with the use of personal interviews with the managers responsible for the social and marketing programs of the companies and a documental research in the means of communication provided and/or collected in the companies as magazines, newspapers, folders, videos, social balance. The data interpretation was done following the content analyses technique and with the use of the software QSR NVIVO. The data shows the communication of the companies, which the social values are included, is focused in specific stakeholders and it is done using certain means, specially written, and it aims to inform the stakeholders about what the company does and the causes and people helped and to involve them to participate in those programs. The managers believe to have achieved some results as the strengthen of the corporate brand, more participation in the programs and an opening of the markets. Besides that there are not many measured data.